2019
DOI: 10.7759/cureus.5391
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Xpert MTB/RIF in Sputum Smear-Negative Pulmonary Tuberculosis

Abstract: IntroductionTuberculosis is a major health problem in Pakistan. The prevalence of pulmonary as well as extrapulmonary tuberculosis is quite high. Tuberculin skin test, radiological imaging, and sputum smear microscopy have limitations in the diagnosis of tuberculosis. Xpert MTB/RIF was recently approved for the diagnosis of pulmonary tuberculosis and has shown promising results. The aim of this study was to determine the diagnostic accuracy of Xpert MTB/RIF in sputum smear-negative pulmonary tuberculosis using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
13
3
Order By: Relevance
“…Results of this study revealed that the GeneXpert assay is highly specific for the PTB diagnosis, in accordance with other earlier studies that have also reported this high specificity (Scott et al, 2011;Geleta et al, 2015). On the other hand, we currently recorded high specificity of the GeneXpert with regard to CN-SN pulmonary samples, in contrast to several recent studies which reported lower specificity among smear-negative PTB cases (Kawkitinarong et al, 2017;Ullah et al, 2017;Rasheed et al, 2019). This high specificity of GeneXpert assay suggests that it acts as a rapid test for the diagnosis of PTB in SN specimens, compared to the traditional methods in resource-limited settings.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Results of this study revealed that the GeneXpert assay is highly specific for the PTB diagnosis, in accordance with other earlier studies that have also reported this high specificity (Scott et al, 2011;Geleta et al, 2015). On the other hand, we currently recorded high specificity of the GeneXpert with regard to CN-SN pulmonary samples, in contrast to several recent studies which reported lower specificity among smear-negative PTB cases (Kawkitinarong et al, 2017;Ullah et al, 2017;Rasheed et al, 2019). This high specificity of GeneXpert assay suggests that it acts as a rapid test for the diagnosis of PTB in SN specimens, compared to the traditional methods in resource-limited settings.…”
Section: Discussioncontrasting
confidence: 59%
“…On using culture as the reference standard, results of the present study showed that the overall sensitivity, specificity, PPV, and NPV of the GeneXpert assay for the pulmonary samples were higher than other previous studies from China (Ou et al, 2015) and Ethiopia (Geleta et al, 2015). Moreover, the sensitivity for CP-SN was also higher than that recently reported by the study of Rasheed et al, (2019). This detected variation in sensitivities between the different studies could be attributed to the population studied, genetic differences, and the relative different prevalence of TB among the various populations.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In this study, the case detection rate of GeneXpert was compared with the conventional smear microscopy and revealed that it showed almost two-fold case detection rate. All patients who turned positive for smear AFB were also positive for GeneXpert, implying that it can replace the conventional smear AFB microscopy in the clinical care of TB [ 9 , 12 , 13 ]. GeneXpert detected additional 31.6% among smear AFB negative cases which is congruent with the finding of the study from north-western part of Ethiopia and other multicenter studies [ 1 , 4 , 7 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified 50 articles: 17 [7,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] in the adult BAL group, 14 [35,[40][41][42][43][44][45][46][47][48][49][50][51][52] in the adult ES group, 7 [35,45,50,[53][54][55][56] in the adult IS group, 2 [57,58] in the pediatric ES group, 6 [57,[59][60][61][62][63] in the pediatric GA group, and 9 [59,[64][65][66][67]…”
Section: Studies' Characteristicsmentioning
confidence: 99%